2020
DOI: 10.1002/jctb.6541
|View full text |Cite
|
Sign up to set email alerts
|

Sieving process selects sugarcane bagasse with lower recalcitrance to xylan solubilization

Abstract: BACKGROUNDSugarcane bagasse is a heterogeneous and organized material that needs a pretreatment to access the polysaccharides (cellulose and xylan). The particle size of a non‐milled bagasse can influence the xylan and xylose solubilization, as well as the enzymatic hydrolysis of the pretreated material. Using bagasse selected on 16‐, 30‐, 40‐ and 50‐mesh sieves: xylan solubilization was performed with hydrogen peroxide; xylose was solubilized with diluted sulfuric acid; and enzymatic hydrolysis was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The alkaline extraction was performed with 6% H2O2 m/v at 25 °C overnight for 4 hours (Alves et al, 2020;Brienzo et al, 2009), calculating the yield of extracted xylan and quantifying the presence of insoluble lignin (Golveia et al, 2009). The solubility of the extracted xylan was determined by making a 1% xylan solution in 50 mmol/L sodium acetate buffer, pH 4.8, according to ALVES (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The alkaline extraction was performed with 6% H2O2 m/v at 25 °C overnight for 4 hours (Alves et al, 2020;Brienzo et al, 2009), calculating the yield of extracted xylan and quantifying the presence of insoluble lignin (Golveia et al, 2009). The solubility of the extracted xylan was determined by making a 1% xylan solution in 50 mmol/L sodium acetate buffer, pH 4.8, according to ALVES (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, xylan exhibited a significant decrease from 21.3% to 9.1% post-acid treatment, as The reduction in xylan by 77.3% in the cellulignin indicates the effectiveness of the pretreatment using a low-concentration of sulfuric acid (2% w/v) and a short reaction time (20 min) in our study. In fact, Alves et al [34] reported a 71.4% xylan removal using 2% (w/v) H 2 SO 4 to treat the 10% SCB at 121 • C, but with autoclaving for a longer reaction time (60 min). Similarly, Hans et al [35] optimized the SCB treatment using 1.5% H 2 SO 4 , 12.5% (w/v) solid loading, and 37 min in an autoclave, removing 75% of xylan.…”
Section: Diluted Sulfuric Acid Pretreatmentmentioning
confidence: 99%
“…The xylan solubility was determined by preparing a 1% xylan solution in sodium acetate buffer 50 mmol/L, pH 4.8 [5]. The solution was heated up to the boiling point in a microwave oven; then, the solution was cooled and remained under 80 rpm agitation for one night at 25 • C. The solution was centrifuged at 10,000× g for 15 min to separate the insoluble material (not solubilized xylan).…”
Section: Xylan Solubility and Solution Conductivitymentioning
confidence: 99%
“…These components represent around 90% of the dry mass of the bagasse; the remaining 10% consists of extractives and ashes [3]. These macromolecules are highly organized in the plant cell wall, which provides high recalcitrance for this biomass to be converted into bioethanol [4], and for its macromolecules to be solubilized [1,5]. Xylan is an interesting polysaccharide to work with as feedstock for several industrial products.…”
Section: Introductionmentioning
confidence: 99%